Evaluasi Kinerja Keuangan Daerah 2010 dan Estimasi 2011, Studi Kasus: Kabupaten Lombok Barat, NTB - Diswandi Diswandi (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2011)
The aim of this research are to evaluate the performance of public finance in 2010 and its estimation in 2011 of West Lombok Regency, NTB. This research calculates secondary data of government budget from income and spending sides. The analysis tool are fitted ratio, fiscal independency ratio, and fiscal interdependency ratio. The results show there are low performance of public finance by local government and highly fiscal interdependency. Government spending is more used to finance indirect expenditure likes daily activities of local government. Keywords: exchange rate, import, gross domestic product, world oil price